Growth through Innovation : An Industrial Strategy for Shanghai - Yusuf, Shahid; Nabeshima, Kaoru (World Bank, Washington, DC, 2014)
In broad terms, the sources of economic growth are well understood but relatively few countries have succeeded in effectively harnessing this knowledge for policy purposes so as to sustain high rates of growth over an extended period of time (commission on growth and development 2008; Yusuf 2009a). This study argues, however, that a high growth strategy which puts technology upgrading and innovation at the center might warrant a different approach from the one currently favored. It derives from the experience of global cities such as New York and London and the empirical research on industrial performance and on innovation. This has yielded four significant findings: first, monosectoral services based economies grow slowly because they benefit less from increases in productivity and from innovation. Second, manufacturing industries producing complex capital goods, electronic equipment, and sophisticated components are more Research and Development (R&D) intensive, generate many more innovations, are more export oriented, have a solid track record of rising productivity, and having achieved competitiveness, are in a better position to sustain it because the entry barriers to these industries tend to be higher. By giving rise to dense backward and forward linkages these industries can serve as the nuclei of urban clusters and maximize employment generation. Third, industrial cities create many more jobs for a middle class and tend to have a more equal distribution of income than cities which are dominated by services. Fourth, and finally, cities with a world class tertiary education and research infrastructure linked to industry, are more resilient in the face of shocks, more innovative, and better able to reinvent themselves.